Effects of antioxidants extracted from leaves of "banaba" (Lagerstroemia speciosa, L.), mangosteen (Garcinia mangostana, L.) and "tsaang gubat" (Ehretia microphylla, L.) on the oxidation stability of biodiesel from Jatropha curcas, L. - Movillon, Jovita L.; Demafelis, Rex B.; Bautista, Ramer P.; Lacsa, Marinella C.; Viray, Donna Marie C.; Cordova, Karel J. (2011)
The stability of biodiesel is relatively inferior to petrodiesel due to its unsaturated fatty acids which may lead to the formation of gums. In the presence of air oxygen, alcohol and acid may be produced which can reduce the flash point and increase the total acid number, thus causing damage to the engines. The effects of the antioxidant extract from "banaba" (Lagerstroemia speciosa, L.), mangosteen (Garcinia mangostana, L.), and "tsaang gubat" (Ehretia microphylla, L.) on the oxidative stability of biodiesel from Jatropha curcas, L. were determined based on the induction period (IP) of the samples using the Rancimat method of oil stability index. The data obtained for the "banaba", mangosteen, and "tsaang gubat"extracts had regression coefficients (R^2) of 0.687, 0.804, and 0.886, respectively, indicating a linear positive correlation between the loading rates (mg total polyhenol in the extracts /L biodiesel; ppm) and the IP (hours). To meet the European standard of 6-hour IP, the loading rtes (g antioxidants per 100 L biodiesel) were found to be: 983.4, 110.9, 1124.9, and 206.3 for "banaba", mangosteen, "tsaang gubat" and the commercial antioxidant respectively. The antioxidant extract from mangosteen leaves had actual loading rate of 260.4 g/100L, with an induction period of 17.52 hours, greatly exceeding the American, European, and Japanese standards.
Keywords: Mangosteen; Banaba; Tsaang Gubat; Jatropha; Biodiesel fuels